Is `waste' an appropriate concept in a sustainable bioeconomy? - Ronald Halim; Ajay Iyer; Sara M. Esteves; Sarah Milliken; Katalin Kalai; Daniel Pleissner; Loreena Stephan; Imene Chentir; Osama Ahmed; Waâd Nasri; Sameh Mohamed; Nils-Kåre Birkeland; et al. (Sustainable Chemistry One World, 2025)
Valorisation of agri-food waste is an essential aspect of creating sustainable circular food systems. The European Research Area Network Cofund Food Systems and Climate (FOSC) and the SUSFOOD2 ERA-Net Cofund supported eight projects focusing on the valorisation of waste generated during primary production or food processing. The projects identified barriers related to the technological, socio-economic, legislative, and institutional challenges of developing a circular food system, and concluded that overcoming these barriers and promoting a circular bioeconomy requires a comprehensive approach involving multiple stakeholders, including fostering supportive policies, and addressing regulatory concerns. The collective experience of the eight projects demonstrates that it is essential to rethink the limitations imposed by the term `waste', and instead to consider all agri-food residues as side streams which have the potential to be valorised as resources for food and feed production if they can be proven as safe to return to the food chain.
Keywords: 330; bioeconomy; valorisation; agri-food waste; circular food systems; legislation